PELAKSANAAN PENYUSUNAN ANGGARAN PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) - ARINI YULIANA SARI (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2017)
This research aimed to find out the budgeting implementation of regionalofKotawaringin Timur District. Nowadays, the budgeting implementation is not based on the real need, the usage of budget is not communicated well to the unit which has proposed, the implementation is less involved in fund-raising and the area which will become target of activity is not planned clearly and there is no open information, performance target is not clear and irregular and also the plan is not suitable with the needs. In budgeting implementation inKotawaringin Timur District still has many problems so that it has not can created optimal preparation. The problems follow: 1.The lack of professional human resources (about quality and quantity) in regional work unit or suitable with the job. 2.Budgeting of regional work unit has not been effective. The type of this research was qualitative descriptive,the collecting data technique were observation, interview and documentation. The data source of this research was from head of planning of control of regional development, sub-field of programming, sub-field of general and staffing, sub-field of finance and sub-field of report planning.             This result of the research showed that in budgeting of regional development department inKotawaringin Timur District was still slow so that there has not been optimal preparation, Factor support, capability in using online application and computer, inhibiting factor, limit and infrastructure which has not been enough. For the conclusion, Regional Development Department ofKotawaringinTimur District still needs improvement to budgeting for development and implementing the function and evaluation of regional development planning. For the suggestion, Regional Development Department should increase the quality of public service and efficiency and effectiveness of governance and budgeting. It still needs accuracy in budgeting or implementing the function and evaluation of regional development planning.